Counterpoise Correction on the Geometries and Vibrational Frequencies of Acetazolamide Dimers - E. Ozel, Aysen; Kecel Gunduz, Serda; Celik, Sefa; Akyuz, Sevim (Asian Journal of Chemistry, 2013)
Acetazolamide (m.f. C4H5N4O3S2) (N-(5-sulfamoyl-1,3,4-thiadiazol-2-yl)acetamide), is a sulfonamide derivative and carbonic anhydrase inhibitor. It is often used in the treatment of various diseases. In this study, the effect of the counterpoise correction of the basis set superposition errors (BSSE) on the geometries, interaction energies and vibrational wavenumbers of four more stable acetazolamide dimers have been analyzed at the DFT/B3LYP level of theory, using 6-31++G(d,p) basis set. The difference in the basis set superposition error corrected (-72.39 kj/mol) and uncorrected (-77.72 kj/mol) interaction energy of the most stable acetazolamide dimer (dimer I ) indicates the magnitude of error caused due to the basis set superposition. The counterpoise correction increases the H-bond distance and decreases the wavenumbers of the intermolecular modes compared to the results of calculations without the basis set superposition error-correction.